If you could see the sun - Liang, Ann (Young adult author) (2022)
"Alice Sun has always felt invisible at her elite Beijing international boarding school...When her parents drop the news that they can no longer afford her tuition, even with the scholarship, Alice hatches a plan to monetize her strange new power--she'll discover the scandalous secrets her classmates want to know, for a price. But as the tasks escalate from petty scandals to actual crimes, Alice must decide if it's worth losing her conscience--or even her life"--
Keywords: Chinese Americans -- Juvenile fiction; International schools -- Juvenile fiction; Schools -- Juvenile fiction; Extortion -- Juvenile fiction; Young adult fiction; Beijing (China) -- Juvenile fiction; School fiction